Endogenous Metabolites Released by Sanitized Sprouting Alfalfa Seed Inhibit the Growth of Salmonella enterica - Ga-Hee Ban (American Society for Microbiology, 2021)
ABSTRACT Sprouts are the leading cause of foodborne disease outbreaks globally, mainly because the specialized conditions required to germinate seed sprouts for human consumption contribute to an environment that allows pathogenic bacteria to flourish. To reduce risk of illness, current food safety guidelines in the United States and Canada recommend hypochlorite treatment for seed sanitation. However, many growers and consumers have become wary of the impact of hypochlorite on human health and the environment and are actively seeking less caustic approaches. Here, we evaluated the effects of both the traditional hypochlorite treatment and a milder alternative on nontyphoidal Salmonella enterica colonization of germinating alfalfa seed. Moreover, we explored three biological factors as potential contributors for inhibition of S. enterica growth: colonization by indigenous bacteria, seed composition changes, and seed metabolite release. In this experimental setting, we found that a combinatorial treatment of heat, peroxide, and acetic acid was as effective as hypochlorite for inhibiting S. enterica growth. Notably, we pinpointed N-acetyl-spermidine as an endogenous metabolite exuded by treated seeds that strongly inhibits S. enterica growth. In doing so, we both elucidated one of the mechanisms of chemical sanitation and highlighted a potential seed-derived mode of antimicrobial treatment that may apply to modernized food safety protocols. IMPORTANCE Warm, humid, and nutrient-rich conditions that are used to produce sprouts encourage Salmonella enterica to proliferate. However, many disparate sanitation methods exist, and there is currently no single treatment that can guarantee pathogen-free seeds. Here, we compared the ability of traditional hypochlorite treatment against a combinatorial treatment of heat, peroxide, and vinegar (HPA) commonly used in organic farming practices to inhibit S. enterica colonization and growth during alfalfa germination and found HPA to be at least as effective. Furthermore, we explored seed-based changes following sanitization treatments using metabolomics and identified polyamines as strong inhibitors of Salmonella growth on germinating alfalfa. Our findings enable a better understanding of host-pathogen interactions in sprout microbial communities and promote in-depth, evidence-based research in seed sprout safety.